Pengaruh Quality of Work Life dan Kepuasan Kerja terhadap Kinerja Karyawan dengan Komitmen Organisasional sebagai Variabel Mediasi - Putra, I Made Dwija Pramana; Sunariani, Ni Nyoman; Mahyuni, Luh Putu (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study is aimed at investigating the influence of quality of work life, job satisfaction, and the role of organizational commitment as mediation on the performance of Perumda Tirta Amertha Buana employees. This study was carried out using a quantitative approach with the target population being employees of Perumda Tirta Amertha Buana. Through census sampling, the entire population, namely 379 employees, were used as research respondents. Empirical data was collected through questionnaires which were then analyzed using the Structural Equation Modeling (SEM) approach with SmartPLS. The test results prove that quality of work life, job satisfaction, and organizational commitment have been proven to have a significant positive influence on employee performance and organizational commitment. Then, organizational commitment is able to play its role as a mediator between the relationship between quality of work life and job satisfaction with employee performance. It is hoped that this study will be able to make a positive contribution to Perumda Tirta Amertha Buana to be able to develop strategic steps to improve employee performance and become a basis and provide deeper insight for future researchers